Front Cover: Computationally Empowered Workflow Identifies Novel Covalent Allosteric Binders for KRASG12C (ChemMedChem 10/2020). (19th May 2020) - Mortier, Jérémie; Friberg, Anders; Badock, Volker; Moosmayer, Dieter; Schroeder, Jens; Steigemann, Patrick; Siegel, Franziska; Gradl, Stefan; Bauser, Marcus; Hillig, Roman C.; Briem, Hans; Eis, Knut; et al.
Abstract : The Front Cover illustrates a novel inhibitor covalently bound to KRAS G12C with an unprecedented mode of binding (image made with LigandScout). This discovery is the outcome of a computationally driven workflow based on the enumeration of novel chemical matter and stepwise prioritization. The most promising compounds were synthesized, biochemically tested, and co‐crystallized with KRAS G12C . More information can be found in the Communication by Jérémie Mortier, Duy Nguyen, Clara D.Christ et al.